Exploring the scope of ecosystem services in diverse farming systems for sustainable agriculture: A review - Lokeshwar , Kesamreddy; Somasundaram, E; Suganthy, M; Krishnan, R; Janaki, P; Parameswari, E; Asritha, M; Vinitha, N (Plant Science Today, 2025)
Ecosystem services (ES) are fundamental to promoting agricultural sustainability, playing a vital role in enhancing resilience and productivity within agricultural ecosystems. This review critically examines the interactions between biodiversity, farming practices and ES delivery, presenting a novel synthesis of their roles in sustainable agriculture. Unlike existing literature focussing on isolated ES or individual farming paradigms, this review integrates insights from multiple agricultural paradigms, including organic, regenerative and conventional systems. It provides a comparative assessment of their effects on biodiversity and ecosystem functionality. It also emphasizes the role of agricultural biodiversity as a nexus for enhancing ecosystem services. This review is structured into four main sections. It begins by classifying key ecosystem services relevant to agricultural systems, underscoring their importance for environmental sustainability. Second, it investigates various farming systems, with a particular focus on the role of biodiversity in enhancing ecosystem services. Third, it conducts a comparative assessment of diverse farming systems follows, evaluating their impacts on biodiversity and ecosystem functionality to inform evidence-based strategies for enhancing ES. This review bridges gaps in existing research by highlighting synergies and proposing strategies to optimize diverse farming systems. These efforts aim to enhance ecosystem services and contribute to sustainable agricultural landscapes.